Importance of deep water uptake in tropical eucalypt forest - Christina, Mathias; Nouvellon, Yann; Laclau, Jean-Paul; Stape, Jose L.; Bouillet, Jean-Pierre; Lambais, George R.; le Maire, Guerric (Functional ecology, 2017)
Summary Climate models predict that the frequency, intensity and duration of drought events will increase in tropical regions. Although water withdrawal from deep soil layers is generally considered to be an efficient adaptation to drought, there is little information on the role played by deep roots in tropical forests. Tropical Eucalyptus plantations managed in short rotation cycles are simple forest ecosystems that may provide an insight into the water use by trees in tropical forests. The contribution made by water withdrawn from deep soil layers to the water required for evapotranspiration was quantified daily from planting to harvesting age for a Eucalyptus grandis stand using a soil water transfer model coupled with an ecophysiological forest model (MAESPA). The model was parameterized using an extensive data set and validated using time series of the soil water content down to a depth of 10 m and water‐table level, as well as evapotranspiration measured using eddy covariance. Fast root growth after planting provided access to large quantities of water stored in deep soil layers over the first 2 years. Eucalyptus roots reached the water‐table at a depth of 12 m after 2 years. Although the mean water withdrawal from depths of over 10 m amounted to only 5% of canopy transpiration from planting to a harvesting age of 5 years, the proportion of water taken up near the water‐table was much higher during dry periods. The water‐table rose from 18 to 12 m below‐ground over 2 years after the harvest of the previous stand and then fell until harvesting age as evapotranspiration rates exceeded the annual rainfall. Deep rooting is an efficient strategy to increase the amount of water available for the trees, allowing the uptake of transient gravitational water and possibly giving access to a deep water‐table. Deep soil layers have an important buffer role for large amounts of water stored during the wet season that is taken up by trees during dry periods. Our study confirms that deep rooting could be a major mechanism explaining high transpiration rates throughout the year in many tropical forests. Lay Summary